Prazer, desejo e razão na ética aristotélica - Vedana, Simone Teresinha (My University, 2015)
This paper proposes to examine the formation of human character according to its sources of pleasures, desires and reason for the study and analysis of the Aristotelian virtues theory. The proposed problem consists to understand in which mesure the irrational part of the soul headed by desires, contributes or not in the formation of human character and how it relates to the rational part of the soul, according to the Nicomachean Ethics. From this perspective, it highlights the importance of pleasurable and painful sensations in the distinction and identification of good and bad moral and seeks to understand the types of desires and pleasures of the body and of the soul and also, their role in the practice of moral and intellectual virtues.From this exhibition of the virtuous and vicious desires, it points the need to learn to wish correctly, as a necessary condition for the practical knowledge performane of the prudent and virtuous man. The study denouement tries to clarify the domain of the reason over the desires and the influence of the reason for the pursuit of the greater good, which the Aristotelian theory understands to be happiness.
O presente trabalho objetiva examinar a formação do caráter humano segundo suas fontes de prazer, desejo e razão através do estudo e análise da teoria das virtudes aristotélicas. O problema proposto consiste em compreender em que medida a parte da alma irracional comandada pelos desejos contribui ou não na formação do caráter humano, e como eles se relacionam com a parte racional da alma, abordada na Ética Nicomaquéia. Nessa perspectiva, destaca-se a importância das sensações prazerosas e dolorosas na distinção e identificação do bem e do mal moral procurando entender os tipos de desejos e prazeres do corpo e da alma e, ainda, o papel deles na prática das virtudes morais e intelectuais. A partir da exposição dos desejos virtuosos e viciosos, evidencia-se a necessidade de aprender a desejar corretamente como condição necessária para a aquisição da sabedoria prática do homem prudente e virtuoso. O desfecho do estudo tenta esclarecer o domínio da razão sobre os desejos, e a influência da razão para a busca do ma ior bem a partir do que a teoria aristotélica compreende ser a felicidade.
Keywords: Aristóteles; Ética; Prazer; Razão; Virtudes; Felicidade; Ethics; Pleasure; Reason; Virtues; Happiness